Preference of Oral Tenofovir Disoproxil Fumarate/Emtricitabine Versus Rectal Tenofovir Reduced-Glycerin 1% Gel Regimens for HIV Prevention Among Cisgender Men and Transgender Women Who Engage in Receptive Anal Intercourse with Men - Alex Carballo-Diéguez (2018)
© 2017, Springer Science+Business Media, LLC, part of Springer Nature. Oral pre-exposure prophylaxis (PrEP) can prevent HIV transmission. Yet, some may prefer not to take systemic daily medication. MTN-017 was a 3-period, phase 2 safety and acceptability study of microbicide gel applied rectally either daily or before and after receptive anal intercourse (RAI), compared to daily oral tablet. At baseline, cisgender men and transgender women who reported RAI (N = 187) rated the daily oral regimen higher in overall liking, ease of use, and likelihood of future use than the gel regimens. After trying all three, 28% liked daily oral the least. Gel did not affect sexual enjoyment (88%) or improved it (7–8%). Most partners had no reaction to gel use. Ease of gel use improved significantly between the first and the last few times of daily use. A rectal gel used before and after RAI may constitute an attractive alternative to daily tablet. Experience with product use may increase acceptability.